Filsafat Digital Integral: Reformulasi Program Literasi Digital Nasional di Era Pandemi Covid-19 di Indonesia - Riyanto, Waryani Fajar; Abror, Robby Habiba (FIKRAH, 2021)
The Covid-19 pandemic has accelerated the process of human migration from the real world to the virtual world (cyber). One of the impacts is the emergence of the phenomenon of cyber religion. As one of the parties responsible for literacy of its citizens in this regard, the government, through the role of the Ministry of Communication and Information, then initiated the National Digital Literacy Program, which is based on four pillars, namely: digital safety, digital skills, digital ethics, and digital culture. In dealing with the cyber religion phenomenon, the four pillars only reinforce the interobjective space. Therefore, to complete it, this research uses the theoretical framework of Ken Wilber's Universal Integralism or Holonic Integralism, which integrates four dimensions of "space" integrally, namely: intersubjective, interobjective, subjective, and objective space. In his findings, the researcher offers the concept of Integral Digital Philosophy, which integrates the four spaces simultaneously. The implications of this finding are beneficial for the provision of religious preachers about the importance of integrating the awareness of the "four worlds" when preaching in cyberspace.